2002
DOI: 10.1039/b209937n
|View full text |Cite
|
Sign up to set email alerts
|

[Cu(i)(bpp)]BF4: the first extended coordination network prepared solvothermally in an ionic liquid solvent

Abstract: Use of an ionic liquid [bmim][BF4] (bmim = 1-butyl-3-methylimidazolium) as solvent has resulted in the first extended coordination structure, the two-dimensional network [Cu(bpp)]BF4 [bpp = 1,3-bis(4-pyridyl)propane], produced via a solvothermal route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
113
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(114 citation statements)
references
References 22 publications
0
113
0
1
Order By: Relevance
“…The precursors in all these cases are the corresponding carbonyl complexes [Fe(CO) 5 and Ni(CO) 4 ], which are not soluble in (BMI + )(PF 6 -) and (BMI + )(BF 4 -) ionic liquids. It is well known that pentacarbonyliron and tetracarbonylnickel yield amorphous iron and amorphous nickel when sonicated in decalin (or any other nonvolatile organic solvent) under argon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The precursors in all these cases are the corresponding carbonyl complexes [Fe(CO) 5 and Ni(CO) 4 ], which are not soluble in (BMI + )(PF 6 -) and (BMI + )(BF 4 -) ionic liquids. It is well known that pentacarbonyliron and tetracarbonylnickel yield amorphous iron and amorphous nickel when sonicated in decalin (or any other nonvolatile organic solvent) under argon.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that pentacarbonyliron and tetracarbonylnickel yield amorphous iron and amorphous nickel when sonicated in decalin (or any other nonvolatile organic solvent) under argon. [7a,7b] On the other hand, the decomposition of Fe(CO) 5 and Ni(CO) 4 in decalin under oxygen yields amorphous metal oxides. [8] The sonochemical decomposition of these carbonyl complexes in (BMI + )(PF 6 -) and (BMI + )(BF 4 -) form crystalline products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] They also offer fascinating possibilities for fundamental studies of their effects on chemical reactions and synthetic processes. [1][2][3]11] In contrast to their application in organic chemistry, the use of RTILs in inorganic synthesis is still in its infancy. There have been only a few reports on the formation and stabilization, by using RTILs, of hollow TiO 2 microspheres, [12] and nanoparticles of palladium, [13] iridium [14] and platinum [15] that are recyclable catalysts for biphasic hydrogenation.…”
mentioning
confidence: 99%
“…These interactions are found in inorganic lattices, polynuclear compounds with bridging ligands [2] or stabilized by electrostatic interactions, [4] and polymeric systems, such as infinite ···Cu-ligand-Cu··· chains with short sideways Cu i ···Cu i interactions. [5] The existence of ligand-bridged Cu i ···Cu i interactions is supported by spectral evidence [6] and has been examined by a series of theoretical calculations, which have sometimes reached different conclusions. [7] However, a recent comprehensive analysis [8] has shown that only a small part of the intermolecular interaction energy is often gained in the ground state from the Cu i ···Cu i interaction, whereas a large component results from Cu i ···ligand interactions, even in the case of ligand-unsupported Cu i ···Cu i species.…”
mentioning
confidence: 98%